Denpasar Youth Festival: Digital Innovation in Increasing the Creativity and Productivity of The Youth Generation - I Wayan Mirta; I Made Wimas Candranegara; Ni Made Anggriyani (Indonesian Association for Public Administration (IAPA), 2022)
The Denpasar Youth Festival program is a program initiated by the Denpasar City Government to accommodate the creativity and productivity of the young generation of Denpasar City. This program also accommodates MSMEs in Denpasar City, especially those owned by the younger generation in Denpasar City in developing their business. This study aims to determine how successful the implementation of this program is considering the implementation of this program in the midst of the covid-19 pandemic. The focus of this research is on policy implementation, namely the Denpasar City Government and Policy Recipients, namely the Denpasar youth generation. The urgency in this study is the pandemic condition that has resulted in many MSMEs, especially those owned by the younger generation of Denpasar City, who have difficulty in marketing their products. The research method used is a qualitative research method. The results of this study are the Denpasar Youth Festival activities are able to facilitate the younger generation in increasing the productivity and creativity of young entrepreneurs in Denpasar City, but the obstacles faced are in terms of their product sales which decreased during the pandemic because purchasing power tends to decrease.